Selective sodium-glucose cotransporter-2 inhibitors in the improvement of hemoglobin and hematocrit in patients with type 2 diabetes mellitus: a network meta-analysis - Luo, Yuanyuan; Bai, Ruojing; Zhang, Wei; Qin, Guijun (Frontiers in Endocrinology, 2024)
To compare the effects of different selective sodium-glucose cotransporter-2 inhibitors (SGLT2i) on hemoglobin and hematocrit in patients with type 2 diabetes mellitus (T2DM) with a network meta-analysis (NMA).Methods: Randomized controlled trials (RCTs) on SGLT2i for patients with T2DM were searched in PubMed, Embase, Cochrane Library, and Web of Science from inception of these databases to July 1, 2023. The risk of bias (RoB) tool was used to evaluate the quality of the included studies, and R software was adopted for data analysis.Results: Twenty-two articles were included, involving a total of 14,001 T2DM patients.SGLT2i included empagliflozin, dapagliflozin, and canagliflozin. The NMA results showed that compared with placebo, canagliflozin 100mg, canagliflozin 300mg, dapagliflozin 10mg, dapagliflozin 2mg, dapagliflozin 50mg, dapagliflozin 5mg, empagliflozin 25mg, and dapagliflozin 20mg increased hematocrit in patients with T2DM, while canagliflozin 100mg, canagliflozin 200mg, canagliflozin 300mg increased hemoglobin in patients with T2DM. In addition, the NMA results indicated that canagliflozin 100mg had the best effect on the improvement of hematocrit, and canagliflozin 200mg had the best effect on the improvement of hemoglobin.Based on the existing studies, we concluded that SGLT2i could increase hematocrit and hemoglobin levels in patients with T2DM, and canagliflozin 100mg had the best effect on the improvement of hematocrit, while canagliflozin 200mg had the best effect on the improvement of hemoglobin.